2021
DOI: 10.1128/mcb.00480-20
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing and Cleavage of GLUT8

Abstract: The GLUT (SLC2) family of membrane-associated transporters are described as glucose transporters. However, this family is divided into three classes, and although the regulated transporter activity of Class I proteins is becoming better understood, Class III protein functions continue to be obscure. We have cataloged the relative expression and splicing of SLC2 mRNA isomers in tumors and normal tissues, with a focus on breast tumors and cell lines. mRNA for the Class III protein GLUT8 is the predominant SLC2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…There has been some indication that the Glut8 transporter may be involved in lysosomal glucose release, but conflicting reports exist. Glut8 exhibits an endosomal/lysosomal targeting sequence (61,62), and in Glut8-stably expressing CHO and MB231 cells, Glut8 colocalized with the lysosomal protein Lamp1 and was detected in lysosomal membranes (61,63). Furthermore, inhibition of the lysosome with chloroquine or bafilomycin resulted in an accumulation of Glut8 (63).…”
Section: Lysosomal Glycogenolysismentioning
confidence: 99%
See 1 more Smart Citation
“…There has been some indication that the Glut8 transporter may be involved in lysosomal glucose release, but conflicting reports exist. Glut8 exhibits an endosomal/lysosomal targeting sequence (61,62), and in Glut8-stably expressing CHO and MB231 cells, Glut8 colocalized with the lysosomal protein Lamp1 and was detected in lysosomal membranes (61,63). Furthermore, inhibition of the lysosome with chloroquine or bafilomycin resulted in an accumulation of Glut8 (63).…”
Section: Lysosomal Glycogenolysismentioning
confidence: 99%
“…Other studies show that Glut8 is an insulin-sensitive plasma membrane transporter which participates in cellular glucose uptake in the heart and other tissues (65,66). Yet an in vitro study screening gainand loss-of-function of Glut8, showed that knockdown of Glut8 does not influence 2-deoxyglucose uptake (63). Thus whether Glut8 is operational as a lysosomal glucose transporter and has a role in glycophagy has not been fully elucidated.…”
Section: Lysosomal Glycogenolysismentioning
confidence: 99%
“…The late-endosomal/lysosomal limiting membrane is the cellular hub for various metabolic reactions (e.g., mTORC1 recruitment to the lysosomal membrane, modulation of mitochondrial homeostasis, regulation of protein, and lipid content of the cellular membrane and membranes of various vesicles). Therefore, besides transporting glucose, GLUT8 may also function as a sensor for various metabolites in cellular metabolic homeostasis ( Alexander et al, 2020 ). Some of the GLUT8 is cleaved into N-terminal and C-terminal peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Of its 12 trans- membrane domains, the cleavage occurs at domain 10, which happens to be the only one that is 100% conserved across the species. The full-length and N-terminal cleaved proteins are retained at the endosomal/lysosomal boundary, whereas the carboxy domain accumulates in a different population of vesicles and is unlikely to perform transport ( Alexander et al, 2020 ). GLUT8 is one of several GLUT species that exists as several alternatively spliced mRNA variants, and there is few available data on its functionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation